Analysis the Influence of Financial Behavior on Financial Well-being of Employed People in Batam City - Valentina, Cindy; Dewi Khornida Marheni (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This study aimed to analysis the influence of financial literacy, financial socialization, and financial attitude on financial well-being in Batam City. Nowadays, the fascination with financial well-being is increasing and many researchers have studied financial well-being in their country. This research methodology was quantitative descriptive approaches. The survey data in this paper is primary data and the number of respondents is 156, collected by questionnaire using Google Form. Data was analyzed by using Statistical Program for Social Science (SPSS) analysis model using IBM® SPSS® Statistics software. The result of this study shows that financial literacy and financial socialization has a significant positive effect on financial well-being, meanwhile the variable of financial attitude has an insignificant positive effect on financial well-being, which is contrary to the hypothesis of this study. The limitations of this study are that the number of the respondents used is still being determined because there is no exact data on the number of workers in Batam City and the survey conducted in this study was only through Google Forms. For future researchers who will use the same research topics, it is hoped that they will be able to reach a broader range of research and not only focus at one place and be able to add more independent variables in influencing the financial well-being.